El sujeto del psicoanálisis: más allá de la dicotomía individuo-sociedad (2014)
Through an approach to the notion of subject from a psychoanalytic perspective based on Freud and Lacan, this theoretical paper seeks to discuss the dichotomy between individual psychology and social psychology and that operates even in certain academic fields and debates. The emphasis of this psychoanalytic approach on the symbolic inscription of subjectivity, as well as its introduction of a necessary conceptual distinction between the “subject” and the “I”, contributes to theorize subjectivity beyond any individualist or socio-structuralist reductionism. In order to encourage interdisciplinary discussions, points of convergence and divergence with some psychological and sociological discourses currently hegemonic are also specified at the end. Keywords : subject; social bond; discourses; social psychology